A ENTREPRENEURIAL SPIRIT Pengaruh Pendidikan Ketenagakerjaan dan Kreativitas Terhadap Jiwa Kewirausahaan (Survei pada siswa kelas XI SMA Negeri 1 Majenang 2024) - Subarkah, muhammad rahmat; Kurniawan, Kurniawan; Widyaningrum, Bakti (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The problem in this study is about the entrepreneurial spirit that occurs among students, the purpose of this study is to determine and analyze the effect of entrepreneurship education and creativity in class XI students of SMA Negeri 1 Majenang. This study aims to determine the effect of entrepreneurship education and creativity on the entrepreneurial spirit. The research method used is a survey method with an explanatory research design. The population of this study were all 11th grade students at SMA NEGERI 1 Majenang with a total of 359 students. The sampling technique with proportionate stratified random sampling is saturated sampling and obtained 189 respondents. Data collection techniques using questionnaires and data analysis techniques using normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, R2 coefficient of determination test, T test, and F test. The results showed that 1) There is a positive and significant effect of entrepreneurship education on the Entrepreneurial Spirit with a significant value (0.000 <0.05). 2) There is a positive and significant effect of creativity on the entrepreneurial spirit with a significant value (0.000 <0.05). The conclusion of this study is that there is a positive and significant effect of entrepreneurship education and creativity on the entrepreneurial spirit.